Unbalanced three-phase interleaved LLC resonant converter: current phase angle balancing technique - Hoang Trung Thong; Nguyen Hoang Linh; Hoang Van Canh; Pham Viet Phuong; Nguyen Kien Trung (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Resonant power supplies have the advantage over traditional pulse width modulation (PWM) converters due to their soft switching capabilities. In addition, the output current ripple can be reduced by using three phase interleaving structure. However, this structure also suffers from some disadvantages, such as resonant current imbalance. Most previous solutions have been focused on hardware as adding extra power switches, increasing the cost and volume of the converter. There are not many software solutions due to the difficulty in modeling unbalance three-phase. This paper will propose a smoothly resonant current balancing solution for the three-phase interleaved LLC structure which is based on controlling directly resonant current phase angles (CPAB). This proposed method shows better current balance and response than the old trigonometric current balancing (TCB) method. The proposed technique is also verified by a 48 V 3.6 kW prototype converter and its experimental results.